2018
DOI: 10.1016/j.hrtlng.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of customizing electrocardiography alarms in intensive care units: A mixed methods study

Abstract: Alarm customization is nuanced and requires adequate support to develop safe and effective practices. The challenges identified can inform development of strategies to improve alarm customization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Individualizing alarm thresholds for example is an important first step 29 . Although this suggestion might seem trivial, there is a significant number of staff members that adhere to the default thresholds of the monitoring devices and do not adjust the thresholds according to an individual patient’s need 30 , 31 . This might be either due to lack of time/will or of know-how.…”
Section: Discussionmentioning
confidence: 99%
“…Individualizing alarm thresholds for example is an important first step 29 . Although this suggestion might seem trivial, there is a significant number of staff members that adhere to the default thresholds of the monitoring devices and do not adjust the thresholds according to an individual patient’s need 30 , 31 . This might be either due to lack of time/will or of know-how.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study, 3%–40% of healthcare workers indicated they had never used many of the monitoring functions of a monitor (Sowan et al., 2017). In recent years, the Emergency Care Research Institute reported 216 deaths resulting from improper alarm management (Keller, 2012), and they listed alarm‐related issues as the most important factors affecting the safety of patients in consecutive years (Cvach, 2012; Ruppel, Funk, Clark, et al, 2018; Ruppel, Funk, Kennedy, et al, 2018). The adverse events reported by The Joint Commission that were caused by improper alarm management included 80 deaths, 13 permanent functional impairments and five cases of prolonged hospital stay (Commission, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…How to customize safely is still a challenge in the postoperative period. 28 A recommendation guide on how to customize alarms was used to increase safety and avoid wider alarm limit ranges that could miss a clinically significant change in the patient's HR. 28 Wider alarm limit ranges create the potential for a clinically significant change in the patient's HR to be missed.…”
Section: Discussionmentioning
confidence: 99%